If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10X + -30 = 360 Reorder the terms: -30 + 10X = 360 Solving -30 + 10X = 360 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 10X = 360 + 30 Combine like terms: -30 + 30 = 0 0 + 10X = 360 + 30 10X = 360 + 30 Combine like terms: 360 + 30 = 390 10X = 390 Divide each side by '10'. X = 39 Simplifying X = 39
| f(-3)=x^3+5 | | 5e-2(4-3e)-2e=10 | | -4.3-2*13.2= | | .5x-1.7=.3-1 | | 4p-13=3p-9 | | Q=7(3.14)v | | -6c-3(c+7)=24 | | -4.3-2(13.2)= | | 126m^2-113-63= | | 5n-2(n-2)=12 | | 2x^2-x+11=0 | | 4n=24n-20-3 | | 6x+8y=54 | | (3/5)=(1/3)+f | | 6x-2(x-1)=-3+7x+11 | | -5n-(-3-3n)=-4 | | 10-7x=38 | | 2b-6-11b-7= | | Y=3(2x-1)-2(5-3x) | | 0.55x+.05(12-x)=.10(76) | | 3(x+1)+3x=x+8 | | 19+3x=50+4x | | 6(x+2)=9x-15 | | 3x-13-5x+4=4-9x-9+3x | | 3*(2(-4)-13)= | | 17-(5m+7)=5+4m-13 | | 16b^2-121=0 | | x^3-5x+2=0 | | 3(x-4)+6=5(x-1) | | 7t+12=2(t+6) | | x^2+4x=-15 | | 7p+8.3=13.9+6p |